TAUHID SEBAGAI PARADIGMA PENDIDIKAN: TINJAUAN FILOSOFIS BERDASARKAN QURAN SURAT AL-ALAQ - Sally Badriya Hisniati; Suryadi, Yadi; Rohimah , Elis; Hambali, Adang; Basri, Hasan (Jurnal Pelita Nusa, 2024)
This article aims to explain the crucial role of Islamic education in integrating religious knowledge with general scientific knowledge. The author attempts to draw a connection that both types of knowledge have synergy when practiced together, especially between the knowledge of tawhid and general sciences. The interrelation between these fields can be positioned within the concepts of rahmaniyah (compassion), takamuliyah (completeness), syumuliyah (comprehensiveness), tawzuniyah (balance), istimroriyah (continuity), wasaliyah (connectivity), rabbaniyah (divinity), and uswiyah (exemplarity). The research method involves a literature review and analysis. The significant differences between religious knowledge and general scientific knowledge are the causes of disintegration, leading to an educational dichotomy. First, Western perspectives often deem religious knowledge as unscientific because its object is not empirical. Second, general scientific knowledge is sensory-based, whereas religious knowledge is often perceived as hallucinatory, despite its sources being the Quran and Hadith, leading to a belief system that is not fully accepted. Third, knowledge that is considered objective in religion may not be easily studied by modern scholars, necessitating a scientific message that ensures the existence of religious knowledge as a source of belief, integrated in a balanced manner in the development of theoretical and practical learning.